Baricitinib Successfully Treated a Teenager with Refractory Livedoid Vasculopathy: A Case Report and Literature Review - Liu C; Jin YY; Han X; Huang H; Bao S; Xu X; Wang L; Jin Y (Journal of Inflammation Research)
Chenxi Liu, Ying-Ying Jin, Xiqiong Han, Hua Huang, Shengfang Bao, Xuemei Xu, Liping Wang, Yanliang Jin Department of Rheumatology and Immunology, Shanghai Children’s Medical Center, Shanghai Jiao Tong University School of Medicine, Shanghai, 200127, People’s Republic of ChinaCorrespondence: Yanliang Jin, Email jinyanliang@scmc.com.cnBackground: The pathogenesis is of livedoid vasculopathy (LV)—a rare, chronic, and recurrent cutaneous vascular obstructive disease—is not fully understood. Conventional anticoagulant therapy sometimes exhibits limited efficacy, and although JAK inhibitors have demonstrated some efficacy in the treatment of refractory LV, the evidence remains insufficient.Case Presentation: This study reports a case of a 14-year-old girl who were failed to maintain remission following treatment with oral rivaroxaban combined with external use of heparin sodium cream. However, the symptoms improved significantly 2 weeks after treatment with baricitinib, and remission was maintained during its gradual reduction.Conclusion: Successful treatment of this refractory patient with baricitinib provides another evidence for the potential therapeutic effect of JAK1/JAK2 inhibitors in LV, and also offers a reference for the dosage tapering regime of baricitinib in LV.Keywords: livedoid vasculopathy, refractory, baricitinib